2022
DOI: 10.1097/dad.0000000000002167
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Myelomonocytic Cell Infiltrate: Use of Next-Generation Sequencing to Diagnose Indeterminate Cell Histiocytosis

Abstract: Indeterminant cell histiocytosis (ICH) is a rare lymphoproliferative disorder that demonstrates features of Langerhans and non-Langerhans cell histiocytoses and diagnosis can be challenging. We present a case of a 62 year old woman with a generalized eruption of erythematous papules on the face, trunk and extremities. Skin biopsies demonstrated a dermal mononuclear cell infiltrate with monocytic (CD4, CD33), histiocytic (CD68, CD163), and dendritic cell (CD1a) immunophenotype but negative for Langerhans' cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…We then selected and included in the study 78 papers, describing 108 patients (Figure 1). 5,8,9,12,32–106 From two case series, we included only some of the described patients, as indicated in Table 1 12,48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then selected and included in the study 78 papers, describing 108 patients (Figure 1). 5,8,9,12,32–106 From two case series, we included only some of the described patients, as indicated in Table 1 12,48 …”
Section: Resultsmentioning
confidence: 99%
“…Molecular analyses were conducted in 27/108 cases (24%). Five out of seven tested cases displayed an ETV3::NCOA2 rearrangement, 68,81,105 while pERK pathway genes mutation was detected in 5/19 tested cases and included two patients bearing KRAS mutation, 79,103 and one case each with an NRAS, 60 MAP2K1, 99 and BRAF V600E point mutation. 75 Two cases bore TET2 mutations.…”
Section: Histopathology and Molecular Biologymentioning
confidence: 99%
“…Recently, amplification of ETV3 has been reported in breast cancer, supporting copy number gain as potent activating mechanism of this oncogene [ 39 ]. Detection of fusion gene ETV3::NCOA2 in independent cell histiocytosis (ICH) underlines a general oncogenic role for ETV3 in hematopoietic malignancies [ 40 , 41 ]. In the myeloid compartment, physiologically expressed ETV3 regulates macrophage differentiation [ 42 , 43 ], highlighting its functional role in developmental processes of myelopoiesis which may be aberrantly reactivated in HL subsets.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the current examples of IDCT with cutaneous symptoms treated with chemotherapy medications to assess the efficacy and safety of chemotherapy drugs 1,5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (Table 1). We found that remission and relapse occurred in 8 out of 26 chemotherapy-treated patients reported to date.…”
Section: Treatmentmentioning
confidence: 99%